PENGARUH PELATIHAN TERHADAP SEMANGAT KERJA PEGAWAI KANTOR CAMAT TOMA-NIAS SELATAN - Duha, Timotius (Jurnal Ekonomi dan Bisnis Nias Selatan, 2023)
The purpose of this study was to determine the effect of training on the morale of the employees of the Toma sub-district office, South Nias Regency. This study determined that all employees of the Toma sub-district office, South Nias Regency, consisted of 30 people as respondents. The research analysis tool used is simple linear regression analysis. The type of data is primary data, obtained from collecting research data through distributing questionnaires. Data were processed using IBM SPPS Statistics 23 software. The results of this study showed that training had a positive and significant effect on employee morale in the Toma sub-district office, South Nias Regency.